2015
DOI: 10.1016/j.ijsu.2015.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of Desarda versus Lichtenstein repair for treatment of primary inguinal hernia

Abstract: Successful inguinal hernia treatment without mesh implantation can be achieved using Desarda repair, as it is effective as the standard Lichtenstein procedure. Shorter operating time, early return to normal gait and lower cost (no mesh) are potential benefits of Desarda repair. The suitability of Desarda repair for patients found to have thin, weak or divided external oblique aponeurosis intraoperatively needs further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 31 publications
(40 reference statements)
11
53
2
1
Order By: Relevance
“…11 In our study we observed that time taken to return to basic activities and work activities was early (3 and 15 days respectively) as seen in various other studies. 11,[19][20][21] In our series foreign body sensation and abdominal wall stiffness at 12 month follow up in 13% and 16% cases was similar to observations in other study also. 11…”
Section: Discussionsupporting
confidence: 91%
“…11 In our study we observed that time taken to return to basic activities and work activities was early (3 and 15 days respectively) as seen in various other studies. 11,[19][20][21] In our series foreign body sensation and abdominal wall stiffness at 12 month follow up in 13% and 16% cases was similar to observations in other study also. 11…”
Section: Discussionsupporting
confidence: 91%
“…18 Youssef T et al, also found operative time significantly less (59.4±6.3 min) compared to Lichtenstein (72±12.2 min). 19 In this study, operative time was taken from start of skin incision to closure of skin. Abbas Z et al, found the operative time similar in both types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] The mean postoperative day 7 Pain Scores in conventional Lichtenstein hernia repair on literature review was 4.45, whereas in present study mean postoperative day 7 pain scores was 3.35.…”
Section: Post-operative Painmentioning
confidence: 74%
“…[8][9][10][11] The mean recurrence in conventional Lichtenstein hernia repair on literature review was 1.20 %, whereas in present study mean recurrence was 0%. [7][8][9][10][11] On comparing the results of present study with literature on conventional Lichtenstein repair we can conclude that cyanoacrylate surgical glue is a reliable method and can be used as an alternative for conventional Lichtenstein hernia repair.…”
Section: -11mentioning
confidence: 76%